Image classification based on sparse-coded features using sparse coding technique for aerial imagery: a hybrid dictionary approach - Qayyum A.; Saeed Malik A.; Saad N.M.; Iqbal M.; Abdullah M.F.; Rasheed W.; Abdullah T.A.B.R.; Bin Jafaar M.Y. (Springer London, 2023)
Aerial photography; Aircraft detection; Antennas; Codes (symbols); Discrete cosine transforms; Discrete wavelet transforms; Glossaries; Image classification; Image coding; Image enhancement; Learning algorithms; Learning systems; Object recognition; Remote sensing; Satellite imagery; Satellites; Unmanned aerial vehicles (UAV); Discrete tchebichef transforms; Discriminative features; Finite Ridgelet Transform; Histogram of oriented gradients; Image processing and computer vision; Scale invariant feature transforms; SIFT; Sparse coding; Classification (of information)